The Killers : A Narrative of Real Life in Philadelphia - Lippard, George, 1822-1854 (Book collections on Project MUSE., 2014)
The Killers is a tale of gang violence, revenge, kidnapping, racial and ethnic conflict, international intrigue, and working-class triumph. Based on the real-life events of a Philadelphia race riot, this long-out-of-print sensational novella showcases the political and literary interests of its author, bestselling novelist George Lippard.